Long-term adaptation to elevated temperature but not CO2 alleviates the negative effects of ultraviolet-B radiation in a marine diatom. (April 2023) - Jin, Peng; Wan, Jiaofeng; Dai, Xiaoying; Zhou, Yunyue; Huang, Jiali; Lin, Jiamin; Lu, Yucong; Liang, Shiman; Xiao, Mengting; Zhao, Jingyuan; Xu, Leyao; Li, Mingke; et al.
Abstract: Multifaceted changes in marine environments as a result of anthropogenic activities are likely to have a compounding impact on the physiology of marine phytoplankton. Most studies on the combined effects of rising p CO2, sea surface temperature, and UVB radiation on marine phytoplankton were only conducted in the short-term, which does not allow to test the adaptive capacity of phytoplankton and associated potential trade-offs. Here, we investigated populations of the diatom Phaeodactylum tricornutum that were long-term (∼3.5 years, ∼3000 generations) adapted to elevated CO2 and/or elevated temperatures, and their physiological responses to short-term (∼2 weeks) exposure of two levels of ultraviolet-B (UVB) radiation. Our results showed that while elevated UVB radiation showed predominantly negative effects on the physiological performance of P. tricornutum regardless of adaptation regimes. Elevated temperature alleviated these effects on most of the measured physiological parameters (e.g., photosynthesis). We also found that elevated CO2 can modulate these antagonistic interactions, and conclude that long-term adaptation to sea surface warming and rising CO2 may alter this diatom's sensitivity to elevated UVB radiation in the environment. Our study provides new insights into marine phytoplankton's long-term responses to the interplay of multiple environmental changes driven by climate change. Highlights: Elevated UVB showed predominantly negative effects on P. tricornutum . Elevated temperature alleviated these negative effects. Elevated CO2 modulated these antagonistic interactions between temperature and UVB.